1997
DOI: 10.1080/00222349708220440
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational dynamics of poly(L-tyrosine)

Abstract: Normal modes and their full dispersions are obtained for the right-handed a-helical poly(L-tyrosine). Optically active modes corresponding to the zone center and at the helical angle are assigned. Both the assignments and the force field are supported by the spectra of N-D species. In addition, modes corresponding to the regions of high density of states and other characteristic features of dispersion curves such as repulsion and exchange of character are discussed. Conformation sensitive modes of other a-heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This mode mainly consists of a mixture of CO wag and NH wag. In poly(l-tyrosine) [8] it is also observed at 766 cm −1 .…”
Section: Backbone Modesmentioning
confidence: 74%
See 2 more Smart Citations
“…This mode mainly consists of a mixture of CO wag and NH wag. In poly(l-tyrosine) [8] it is also observed at 766 cm −1 .…”
Section: Backbone Modesmentioning
confidence: 74%
“…In earlier publications we have reported the vibrational dynamics of biopolymeric systems having ␣, ␤, and 3-fold helical conformations [1][2][3][4][5][6][7][8][9][10][11]. In continuation of these studies, we report in the present communication our work on the vibration dynamics and heat capacity of poly(l-isoleucine) (PLIS).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…In the present case also, this vibration is not isolated within the peptide group and we see that it appears at 1317 cm −1 , matching well with the calculated values 1313 cm −1 . This also agrees well with the amide III band reported at 1299, 1298, and 1313 cm −1 in poly( L ‐leucine),21 poly(β‐benzyl‐ L ‐aspartate),1 and poly(α‐amino isobutyric acid),23 which show α‐helical structure. The amide IV is observed at 480 cm −1 and is calculated at 488 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…PLH is a polypeptide with an imidazole ring in the side chain (Fig. 1), as in case of poly( L ‐tyrosine),18 where a benzene ring is present in the side chain. Pollock and Doocherly19 have reported that PLH can be prepared by polymerization of N ‐carboxyanhydride of L ‐histidine in the presence of a primary or secondary amine.…”
Section: Introductionmentioning
confidence: 99%